EM PROL DA TRAJETÓRIA DELAS: ENTRE OCUPAÇÕES E DESPEJOS NA GRANDE VITÓRIA - ES - Souza, Marina Coelho de (2022)
The present dissertation consists of understanding the presence of women in housing movements in Vitória-ES region, as an essential agent in the claim and promotion of access to housing rights. In this way, the participation of different social agents w